- Empowerment of Pregnant Women, Mothers of Children Under Two, and Older Adults to Enhance Knowledge and Skills for Sustainable Stunting Prevention in Pauh District: - - Wira Iqbal; Agung Kurnia Moses; Veronica Shinta Maharani; Nurul Aisyah Adrian; Aqil Naufal; Abdul Rasyid Hawwari; Bunga Fazia Nola (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2026)
Stunting remains a major public health problem affecting children’s physical growth and cognitive development. In Pauh District, Padang City, the prevalence of stunting reached 9.75% (213 of 2,184 children under five). This study aimed to develop and evaluate the effectiveness of a cross-generational family empowerment model in improving stunting prevention practices. A quasi-experimental design with a pre–post and post-test approach without a control group was employed using a Community-Based Participatory Approach (CBPA), emphasizing active community involvement in all stages of the intervention. The sample consisted of 21 purposively selected participants, including pregnant women, mothers of children under five, and elderly caregivers. The intervention included health education sessions, group discussions, nutrition and exclusive breastfeeding education, positive parenting practices, and home visits. Data were collected using pre- and post-test questionnaires, observation of caregiving practices, and child development monitoring using the Child Development Card. The results showed an increase in mean knowledge scores of 31.43 among elderly caregivers and 68.57 among mothers. Improvements were also observed in dietary practices, hygiene behaviors, and responsive caregiving, with most children achieving age-appropriate development. The novelty of this study lies in the integration of cross-generational family empowerment into a comprehensive community-based intervention model. Scientifically, these findings highlight the importance of involving multi-generational caregivers in stunting prevention and provide policy implications for developing sustainable family-based promotive and preventive programs.